Зумовленість перекладу власних назв правовою значущістю об’єктів номінації - Мозговий, Володимир Іванович; Mozgovoy, V. I. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розглянуто методику перекладу різних розрядів онімної лексики з російської на українську мову, яка має враховувати права власника імені, соціально-правову значущість об’єктів номінації, особливості мовних систем й однаковість підходів до їхньої передачі в споріднених пропріальних культурах. З урахуванням цієї методики запропоновано найбільш показові приклади можливого перекладу власних назв і проаналізовано причини наявних помилок у сучасних номінативних презентаціях. The author reveals the technique of transfer of the main categories of onym lexicon from Russian into Ukrainian, considering the rights of the owner, the social and legal importance of objects of the nomination, feature of language systems and unity of approaches to their functioning in different proprial cultures. The article defines limits of possible changes in lexico-semantic, phonetic-graphic, morphological and spelling «drawing» of a proper name (in this case in the Russian-Ukrainian official context) on the basis of allocation in its structure of specific onym language units – phononyms, graphonyms and morphonyms, capable to keep and adequately transfer legal information about primary or modern owner in related languages. The most indicative examples of the possible translation of proper names are offered and the reasons of mistakes in modern nominative presentations are analyzed.
Conditionality of the Translation of own Names by the Legal Importance of Objects of the Nomination
Keywords: власна назва; proper name; переклад; the translation; розряди власних назв; categories of proper names